A Metagenomics-Based Metabolic Model of Nitrate-Dependent Anaerobic Oxidation of Methane by Methanoperedens-Like Archaea - Arshad, Arslan; Speth, Daan R.; de Graaf, Rob M.; Op den Camp, Huub J. M.; Jetten, Mike S. M.; Welte, Cornelia U. (Frontiers in Microbiology, 2015)
Methane oxidation is an important process to mitigate the emission of the greenhouse gas methane and further exacerbating of climate forcing. Both aerobic and anaerobic microorganisms have been reported to catalyze methane oxidation with only a few possible electron acceptors. Recently, new microorganisms were identified that could couple the oxidation of methane to nitrate or nitrite reduction. Here we investigated such an enrichment culture at the (meta)genomic level to establish a metabolic model of nitrate-driven anaerobic oxidation of methane (nitrate-AOM). Nitrate-AOM is catalyzed by an archaeon closely related to (reverse) methanogens that belongs to the ANME-2d clade, tentatively named Methanoperedens nitroreducens. Methane may be activated by methyl-CoM reductase and subsequently undergo full oxidation to carbon dioxide via reverse methanogenesis. All enzymes of this pathway were present and expressed in the investigated culture. The genome of the archaeal enrichment culture encoded a variety of enzymes involved in an electron transport chain similar to those found in Methanosarcina species with additional features not previously found in methane-converting archaea. Nitrate reduction to nitrite seems to be located in the pseudoperiplasm and may be catalyzed by an unusual Nar-like protein complex. A small part of the resulting nitrite is reduced to ammonium which may be catalyzed by a Nrf-type nitrite reductase. One of the key questions is how electrons from cytoplasmically located reverse methanogenesis reach the nitrate reductase in the pseudoperiplasm. Electron transport in M. nitroreducens probably involves cofactor F420 in the cytoplasm, quinones in the cytoplasmic membrane and cytochrome c in the pseudoperiplasm. The membrane-bound electron transport chain includes F420H2 dehydrogenase and an unusual Rieske/cytochrome b complex. Based on genome and transcriptome studies a tentative model of how central energy metabolism of nitrate-AOM could work is presented and discussed.